Members of the Toc159 Import Receptor Family Represent Distinct Pathways for Protein Targeting to Plastids - Ivanova, Yordanka (The American Society for Cell Biology, 2004)
Plastids represent a diverse group of organelles that perform essential metabolic and signaling functions within all plant cells. The differentiation of specific plastid types relies on the import of selective sets of proteins from among the ∼2500 nucleus-encoded plastid proteins. The Toc159 family of GTPases mediates the initial targeting of proteins to plastids. In Arabidopsis thaliana, the Toc159 family consists of four genes: atTOC159, atTOC132, atTOC120, and atTOC90. In vivo analysis of atToc159 function indicates that it is required specifically for the import of proteins necessary for chloroplast biogenesis. In this report, we demonstrate that atToc120 and atToc132 represent a structurally and functionally unique subclass of protein import receptors. Unlike atToc159, mutants lacking both atToc120 and atToc132 are inviable. Furthermore, atToc120 and atToc132 exhibit preprotein binding properties that are distinct from atToc159. These data indicate that the different members of the Toc159 family represent distinct pathways for protein targeting to plastids and are consistent with the hypothesis that separate pathways have evolved to ensure balanced import of essential proteins during plastid development.